Atmospheric degradation of CH2C(CH3)C(O)OCH3 initiated by OH radicals: Mechanistic study and quantification of CH3C(O)C(O)OCH3 in NOx free air - Gibilisco, Rodrigo Gastón (2015)
The product distribution of the gas-phase reaction of OH radicals with methyl methacrylate (CH2═C(CH3)C(O)OCH3, MMA) in the absence of NOx was studied at 298 K and atmospheric pressure of air. The experiments were performed in a Teflon chamber using solid-phase microextraction (SPME) with GC–MS and GC–FID for product identification and quantification, respectively. In the absence of NOx, methyl pyruvate (CH3C(O)C(O)OCH3) was identified with a yield of 76 ± 13% in accordance with the decomposition of the 1,2-hydroxyalkoxy radicals formed. In addition, a detailed quantum chemical study of the degradation of MMA was performed by density functional theory (DFT) methods using the MPWB1K functional. This calculation suggests that formation of methyl pyruvate, from C1–C2 scission of 1,2-hydroxyalkoxy radical, is kinetically and thermodynamically the most favorable reaction path taking into account the electronic properties of reaction intermediates and transition states. The difference observed on the degradation mechanism of MMA in the presence and absence of NOx was explained in terms of the associated thermochemistry. Furthermore, this study propose that reaction between peroxy radical (RO2•) and hydroxyl radical (OH) became relevant at NOx-free environments. This statement is in agreement with recent studies concerning small peroxy radicals such as CH3OO•.